AVALIAÇÃO SAZONAL DE EXTRATOS AQUOSOS DE Myrciaria glazioviana - BARRETO, Brenda Vitória Ribas; MACHADO, Giovanna Eduarda; DE CASTRO, Thiago Aguayo; CARDOSO, Claudia Andrea Lima (ANAIS DO ENIC, 2026)
.